Earnings Growth and Movements in Self‐Reported Health. (11th August 2016) - Halliday, Timothy J.
Abstract : We employ data from the Panel Study of Income Dynamics to investigate income to health causality. To account for unobserved heterogeneity, we focus on the relationship between earnings growth and changes in self‐reported health status. Causal claims are predicated upon appropriate moment restrictions and specification tests of their validity. We find evidence of causality running from income to health for married women and men. In addition, spousal income appears to be protective for married women.